Studies on Quality Characteristics of Chicken Meat Patties Extended with Oat Flour - Reddy, P. B. Obula; Rao, B. Eswara; Mallika, E. Naga; Rao , T. S.; Reddy , G.V. Bhaskar (Journal of Meat Science, 2016)
The present investigation was carried out to evaluate different levels (2, 3 and 5 percent) of oat flour on quality characteristics of chicken meat patties. Among different treatments, meat patties incorporated with oat flour at 5 per cent level recorded significantly (p0.05) by addition of different levels of oat flour. It was concluded that addition of oat flour at 5 percent level produced excellent quality chicken meat patties.
Keywords: Chicken meat patties; Low-fat; Oat flour; Qualit